Emotional loneliness, perceived stress, and academic burnout of medical students after the COVID-19 pandemic - Malakcioglu, Cem (Frontiers in Psychology, 2024)
Introduction In recent times, emotional loneliness has been increasing among young people, despite their intense social interaction via virtual platforms and in real life. Their social-emotional development seems to be interrupted due to high levels of psychological stress, and it probably results in significant academic problems. This study aimed to investigate the relationships between loneliness, perceived stress, and academic burnout among medical students after the COVID-19 pandemic. Methods Datasets were collected from 630 medical students (51.7% women, with the mean age of 21.31 and the standard deviation of 2.14) by using scales for emotional and social loneliness, psychological stress, and academic burnout in January 2023. After verifying normality, a t-test and ANOVA were used to compare groups. Pearson's correlation coefficient and path analyses were also utilized for data analysis. Results In terms of loneliness, there were significant differences between genders in preclinical and clinical term groups, and stress levels were also significantly different between the two term groups. Men were found to be more emotionally lonely than women. No significant difference was observed for academic burnout across gender and term groups. Perceived stress played a mediator role between emotional loneliness and academic burnout, while social loneliness had almost no effect on either stress or academic burnout. Stress increased significantly as educational levels increased. Conclusions According to the results, emotional loneliness and stress increase academic burnout. To alleviate burnout, emotional loneliness and stress should be decreased through various psychosocial interventions, such as group therapies. Addressing the psychological issues and improving the psychological resilience of medical students can also help.